A study of measurement scenarios for the future CO2M mission: avoidance of detector saturation and the impact on XCO2 retrievals - M. Weimer; M. Hilker; S. Noël; M. Reuter; M. Buchwitz; B. Fuentes Andrade; R. Lang; B. Sierk; Y. Meijer; H. Bovensmann; J. P. Burrows; H. Bösch (Atmospheric Measurement Techniques)
The direct and indirect release of carbon dioxide (CO2) by human activities into the atmosphere has been the main driver of anthropogenic climate change since the industrial revolution. The Paris Agreement from 2015 requires regular country-based reports of greenhouse gas emissions. Inverse modeling of observed concentrations of greenhouse gases is one important approach to verify reported emissions. The future constellation of Copernicus Anthropogenic CO2 Monitoring (CO2M) satellites is dedicated to greenhouse gas measurements with high spectral and spatial resolution and wide coverage. The requirements for the performance of the instruments and retrieval algorithms for the column-averaged dry-air mole fraction (XCO2) are stringent in order to identify, assess and monitor CO2 emissions from space. In this study, we analyze the impact of avoiding detector saturation on the precision and spatial coverage of XCO2. We use the Fast atmOspheric traCe gAs retrievaL (FOCAL) algorithm, which has been selected to be one of the operational greenhouse gas retrieval algorithms to be implemented within the CO2M ground segment. In order to avoid saturation, the number of read-outs per sampling time can be increased and the signals can be co-added on board, which we refer to as “temporal oversampling” in this study. We use a subsampled 1-year dataset of simulated radiances to define the temporal oversampling factors (OSFs) that are sufficient to avoid detector saturation and then apply the defined OSF combinations globally. We find that OSFs larger than 1 will lead to a significant decrease in the number of saturated observations, with some impact on the median XCO2 precision, concluding that OSFs larger than 1 should be considered for the satellite mission. These results are based on simulated radiances. Consequently, the real impact on precision should be analyzed in more detail during the commissioning phase of the satellite.